Examining the Effects of Compensation, Digital Literacy, and Promotion on Employee Performance at BRI Suli Unit - Irfa H, Aulia; Maszudi, Edi; Pratiwi, Indah (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines compensation, digital literacy skills, and promotions in relation to employee performance. This third variable was chosen because it is considered to play an important role in creating a productive and competitive work environment. This research aims to examine compensation, digital literacy skills, and promotion of employee performance at Bank BRI Suli Unit, Luwu Regency, South Sulawesi. The research approach employed is qualitative, utilizing secondary, primary, and tertiary data types. Data collection techniques include interviews, observation, and direct observation. The entire population, consisting of eight informants, was used as the sample. Data is analyzed in depth to identify the quality of employee work. The research results show that the implementation of compensation, digital literacy capabilities, and promotions plays an important and meaningful role in increasing employee productivity, effectiveness, and performance. These third factors support one another in creating optimal performance, which ultimately leads to increased employee satisfaction with their performance. This research recommends that Bank BRI Suli Unit's management continue to develop and support the implementation of these three aspects.